NVESTIGATION OF EXPORT PRICES OF REGIONAL RESOURCES WITH MULTIPLE LINEAR REGRESSION ANALYSIS: HIGH CARBON FERROCHROME SAMPLE - Eşidir, Kamil Abdullah; Çubuk, Muhammed (Sanayi ve Teknoloji Bakanlığı, 2023)
Efficient utilization of resources is of paramount importance in the context of regional development. In this regard, identifying and harnessing the potential of a region is crucial for incorporating it into the economy. To achieve this objective, this study employs a Multiple Linear Regression Analysis to investigate the effect of chrome and ferrochromium trade prices on the export prices of high-carbon ferrochromium, which possesses a significant potential for value-added production and foreign currency revenue. Data for the study was obtained from the Turkish Statistical Institute on a monthly basis for the years 2000-2022 (a total of 270 months). The dependent variable in the model is the monthly export price of high-carbon ferrochromium (Ton/USD), while the independent variables are the monthly import price of high-carbon ferrochromium (Ton/USD), the monthly export price of low-carbon ferrochromium (Ton/USD), the monthly import price of low-carbon ferrochromium (Ton/USD), the monthly export price of chromium (Ton/USD), and the monthly import price of chromium (Ton/USD). The results of the study reveal that the import price of high-carbon ferrochromium and the export price of low-carbon ferrochromium have a significant effect on the export price of high-carbon ferrochromium. The effect of chrome export price, however, is found to be low. Additionally, the study provides recommendations for identifying regional potential.

Kaynakların etkin kullanımı bölgesel kalkınma açısından önem arz etmekte olup bölgenin sahip olduğu potansiyelin ortaya çıkarılarak ekonomiye kazandırılmasına katkı sağlar. Kaynakların verimli kullanılmasının sağlayacağı katma değer göz önünde bulundurularak üretim potansiyeli ve ihracat geliri bakımından, krom ve ferrokrom ürünlerinin dış ticaret fiyatlarının yüksek karbonlu ferrokrom ihracat fiyatına etkisi çoklu doğrusal regresyon analizi ile incelenerek bölgesel kalkınma bakımından önemi açıklanmıştır. Çalışmada kullanılan veriler, Türkiye İstatistik Kurumundan (TÜİK) edinilmiş olup 2000-2022 yıllarını (270 ay) kapsamaktadır. Tasarlanan modelin bağımlı değişkeni, yüksek karbonlu ferrokrom aylık ihracat fiyatı (Ton/USD); bağımsız değişkenleri ise yüksek karbonlu ferrokrom aylık ithalat fiyatı (Ton/USD), düşük karbonlu ferrokrom aylık ihracat fiyatı (Ton/USD), düşük karbonlu ferrokrom aylık ithalat fiyatı (Ton/ USD), krom aylık ihracat fiyatı (Ton/USD) ve krom aylık ithalat fiyatıdır (Ton/USD). İstatistiksel olarak anlamlı çıkan sonuçlara göre, yüksek karbonlu ferrokrom ithalat fiyatı ve düşük karbonlu ferrokrom ihracat fiyatlarının, yüksek karbonlu ferrokrom ihracat fiyatına etkisi yüksektir. Krom ihracat fiyatlarının etkisi ise düşük bulunmuştur. Çalışmada bölgesel potansiyelin değerlendirilmesine yönelik öneriler de getirilmiştir.
ÇOKLU DOĞRUSAL REGRESYON ANALİZİ İLE BÖLGESEL KAYNAKLARIN İHRACAT FİYATLARININ İNCELENMESİ: YÜKSEK KARBONLU FERROKROM ÖRNEĞİ
Keywords: Business Administration; İşletme